Antimicrobial Properties of Pliek U as Traditional Acehnese Fermented Spices - Fauzi Satria; Tri Widyawati; Taufik Sungkar (International Journal of Ecophysiology, 2024)
The high prevalence of antimicrobial resistance globally has increased the burden of disease. The phenomenon demands urgency to explore new antimicrobial drugs, one of which is sourced from natural ingredient, spices. Pliek U, as one of the spices traditionally processed by Acehnese, has attracted researchers to explore its potential source for antimicrobial substances. The objective of this literature review is to explore the characteristic, production, chemical composition, and antimicrobial mechanism of Pliek U. A literature search was carried out on PubMed, Science Direct, Springer Link, and Google Scholar using the keywords "Pliek Uâ€, â€œCoconut Fleshâ€, and â€œAntimicrobialâ€. The articles obtained were then screened based on predetermined criteria. The results of the analysis were displayed in tabular and narrative form. The final result was 8 main articles and 10 additional articles after screening 65 articles obtained from the database. Pliek U powder is traditionally produced and has unique characteristics that make it easy to recognize. Pliek U mechanism of action based on the chemical composition and the role of lactic acid bacteria in the fermentation process. Analysis shows that Pliek U is a promising antimicrobial source, so it needs to be researched and developed further in the pre-clinical to clinical phases.